Methodology of obtaining intrinsic creep property of concrete by flexural deflection test. (March 2019) - Liang, Siming; Wei, Ya
Abstract: The shrinkage of concrete when exposed to external drying influences the accurate quantification of concrete creep. To reduce the effect of shrinkage on the measured creep, particularly for concrete at early ages when the shrinkage is pronounced, a flexural creep test set-up was designed in this study to investigate the creep property of concrete beams with w / c ratios of 0.3 and 0.4 at the age of 7 days. The concrete beams were exposed to both sealed and drying conditions. A sequential coupled hydromechanical finite element analysis was conducted to back-calculate the creep parameters in the original microprestress solidification theory-based creep model from the measured creep-induced deflection. The results show that the flexural creep test is capable of obtaining the intrinsic creep property of concrete without incorporating the shrinkage effect as long as the relative humidity distribution in the concrete beams is symmetric about the neutral plane. The intrinsic creep property depends only on the mixture proportions of concrete, i.e., it is independent of the loading and drying conditions, which can be used to predict the deflection development of concrete beam under other complex drying conditions. The findings in this study provide a new methodology of obtaining concrete creep, which solves the problem of the conventional uniaxial creep testing method that both creep strain and shrinkage strain need to be measured during the creep test.